Optimizing the biodegradation of 3,4-Dichlorobenzoic acid by Corynebacterium jeikeium - Alqudah, Ali Abdallah; Tarawneh, Khaled Ahmed; Alkafaween, Ibrahim Khaled; Saad, Shahbudin (Canadian Center of Science and Education, 2014)
Chlorinated benzoic acids (CBA) have been intentionally released to the environment due to their use in agriculture as herbicides or pesticides, or unintentionally because they are common metabolites in the aerobic transformation of many chlorinated pollutants. The biodegradation of 3,4-dichlorobenzoic acid compound was investigated by using Corynebacterium jeikeium bacteria, which was isolated from Petra wastewater plant in Jordan. 3,4-dichlorobenzoic acid compound (3,4-DCBA) was used as a sole carbon and energy source in minimal salt media (MSM). 3,4-DCBA was the most degradable compound among the Chlorobenzoic acid compounds tested by this bacteria. Different conditions such as substrate concentration, temperature, pH, agitation rate, carbon starvation and carbon adaptation were used to obtain optimal Biodegradation. The optimal conditions for the biodegradation were 3mM as substrate concentration and the culture conditions were also showed a significant impact on the ability of these cells to remove 3,4-DCBA. The optimum solution, temperature and agitation rate were 7.5, 37 °C and 150 rpm, respectively. Adaptation of the cells to 3,4-DCBA for 24 hr and 48 hr and cells starvation for 24 hr and 48 hr increased the initial degradation rate. The degradation ability was monitored through disappearance of the substrate from the medium and the measuring the accompanying chloride release. Corynebacterium jeikeium dioxygenases were physiologically induced by 3,4-DCBA compound. They were analyzed for both ortho or meta ring-cleavage of this aromatic compound. Only 1,2-dioxygenase activity was detected which mean that the cleavage is through the ortho pathway. This microorganism can be a valuable and promising candidate for use in the biotreatment of wastewater samples contaminated with 3,4-DCBA.